Exploring virulence factors, virulome, and multidrug resistance of Klebsiella pneumoniae strains isolated from patients with central Line-associated bloodstream infections - Mohab G. Sayed; Moselhy S. Mansy; Mervat I. El Borhamy; Heba M. Elsherif (Scientific Reports)
Abstract This study aimed to analyze the antibiotic resistance patterns and virulence profiles of Klebsiella pneumoniae, a prevalent gram-negative pathogen linked to CLABSI patients globally. Of a total of 185 microbial isolates, 51 (27.5%) were K. pneumoniae isolates. The results of antimicrobial susceptibility testing using the disk diffusion method were compared to those of the VITEK-2. Phenotypic analysis revealed that 88.3% were biofilm producers and 50.9% were extended-spectrum beta-lactamase (ESBL) producers. Enterobacterial repetitive intergenic consensus-polymerase chain reaction (ERIC-PCR) revealed a discriminatory power of 0.7111 between ten selected isolates. The PCR detection of the virulence genes, including FimH, rmpA, iutA, and fyuA, revealed that the ten selected isolates harbored all these genes, except one without the fyuA gene. The presence of the rmpA and the iutA genes confirmed them as hypervirulent (hv) K. pneumoniae. The genes (EAST-1, CNF-1) were present in 20% and 60% of the isolates, respectively. All isolates had the bla TEM and bla SHV resistance genes, while 50% had the bla NDM carbapenemase resistance gene. In conclusion, all selected K. pneumoniae isolates were proven to be ESBL producers and carbapenem-resistant, highlighting significant multidrug resistance. We found a strong correlation between biofilm formation and multidrug resistance, as well as between phenotypic and genotypic detection of various virulence factors. Infections from hyKp strains represent a growing public threat. Our findings aim to enhance therapeutic options for patients and help reduce complications and mortality.